THE EFFECTIVENESS OF LOKTUAN PUBLIC PORT MANAGEMENT AND DEVELOPMENT IN INCREASING BONTANG CITY'S ORIGINAL REGIONAL REVENUE (PAD) - Wa Ode Ervinna; Ardi Paminto; Abdul Gafur; Wisnu Satria (Universitas Tidar, 2022)
This study aims to determine the effectiveness of the management and development of the Loktuan public port in order to increase the Bontang City's Original Regional Revenue (PAD). This research uses descriptive qualitative research method. The types of data used are primary and secondary data, the instruments in this study are observation, interviews and documentation, using Miles and Hubermen's theoretical analysis techniques. The results showed that the policy of the Bontang City Government as the owner of Loktuan Public Port Assets influenced the management and development of Loktuan Public Port. The role of the Bontang City Government and PT. Pelindo IV (Persero) in increasing Regional Original Revenue from the port sector, by cooperating in the use of port facilities for port services. Loktuan Public Port Management in collaboration with PT. Pelindo IV (Persero) is very effective in increasing Bontang City's Original Revenue from the Port sector. With increasing port operational activities every year, the development of the Loktuan Public port is very effective to be developed through effective cooperation so as to increase Bontang City's Original Revenue from the port sector.